2009
DOI: 10.1590/s0102-695x2009000400005
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização farmacognóstica das folhas e sementes de Albizia lebbeck (L.) Benth. (Fabaceae)

Abstract: RESUMO:Albizia lebbeck (L.) Benth. é popularmente conhecida no Brasil por coração-de-negro. É uma espécie aclimatada nesse país. As sementes dessa espécie são utilizadas no tratamento de diarréia, disenteria e hemorróidas e as folhas, no tratamento de úlceras e nas conjuntivites alérgicas. Este trabalho foi realizado com a finalidade de determinar as características macroscópicas e microscópicas das folhas e sementes dessa planta, uma vez que estas são as partes usadas popularmente. Algumas características de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The presence of sclerenchyma enveloping the vascular system of the midrib is a common feature in Leguminosae species, as was previously reported for Albizia Durazz. (Miranda et al 2009), Bauhinia and Schnella (Pereira et al 2018), and Psoralea L. (Crow et al 1997). According to Dickson (2000), sclerenchyma, being composed of ligni ed cells, provides support and protection for plants; it can occur alone or grouped in bundles.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of sclerenchyma enveloping the vascular system of the midrib is a common feature in Leguminosae species, as was previously reported for Albizia Durazz. (Miranda et al 2009), Bauhinia and Schnella (Pereira et al 2018), and Psoralea L. (Crow et al 1997). According to Dickson (2000), sclerenchyma, being composed of ligni ed cells, provides support and protection for plants; it can occur alone or grouped in bundles.…”
Section: Methodsmentioning
confidence: 99%
“…The leaves (150 g) were dried at room temperature and powered until reaching the granulometry of 850 μm. The powder was submitted to dynamic maceration with solvent renewal using ethylic alcohol 96º GL until vegetal matter depletion (Miranda et al, 2009). Next, the filtrate was concentrated under reduced pressure in a rotary evaporator (Tecnal TE-211 model) at 35 °C, until for obtaining the crude extract (CE).…”
Section: Preparation Of I Laurina Leaf Crude Extractmentioning
confidence: 99%
“…Saponin, macrocyclic alkaloids, phenolic glycosides, coumarins, and flavonols [15][16][17] Specific components [16,18,19] Bark Saponins (named albiziasaponins A, B, and C) [16,17] Root Echinocystic acid (saponin) [15] Pod 3',5 dihydroxy4', 7 dimethoxy flavone and N-benzoyl L Phenyl alaninol Flower different sterols (taxerol, cycloartemol, lupeol, campesterol, and sitosterol) [15] CONTEMPORARY RESEARCH…”
Section: Whole Plantmentioning
confidence: 99%
“…[22] In contrast to above studies, Miranda et al have shown that ethanolic extract of A. lebbeck leaf powder has no inhibitory activity on the growth of Gram-negative (Salmonella typhymurium, E. coli and Salmonella choleraeseus) and Gram-positive (B. cereus, S. aureus, and Micrococcus luteus). [16] Lam and Ng isolated lebbeckalysin from seeds of A. lebbeck which suppressed the growth of E. coli with an IC 50 of 0.52 M. [23] Antifungal Activity Gupta et al (2012) have screened aqueous, acetone, and benzene extract of A. lebbeck for anti-candida activity against Candida albicans results revealed 7, 13, and 6 zone of inhibition in millimetre, 0.60, 0.41, and 0.50 MIC for 50% inhibition and 0.70, 0.55, and 0.65 minimum fungicidal concentration for 50% sensitivity, respectively. [24] Lam and Ng in the study mentioned above also assess the antifungal effect of lebbeckalysin isolated from seeds of A. lebbeck which impeded mycelial growth in the fungi Rhizoctonia solani with an IC 50 of 39 M, but there was no effect on a variety of other filamentous fungi, including Fusarium oxysporum, Helminthosporium maydis, Valsa mali, and Mycosphaerella arachidicola.…”
Section: Antibacterial Activitymentioning
confidence: 99%